TERITORIALITAS DAN KEAMANAN PENGHUNI PADA PERMUKIMAN HORISONTAL DAN VERTIKAL (RUMAH SUSUN SEDERHANA) (Studi Kasus : Rumah Susun Sederhana Sewa (Rusunawa) Bumi Cengkareng Indah, Jakarta ) - Lianto, Fermanto; Dwisusanto, Basuki (Puslitbang Kebijakan dan Penerapan Teknologi (PKPT), Kementerian PUPR, 2015)
Human in daily activities necessary to get security. Concept of territoriality which refers to behavior and social life, withboundaries (physical and non-physical), compromised, preserved and maintained, either individually or in groups, tokeep security and harmony between human and the community. The function of territoriality in basic human needs forsecurity, can be divided into multiple sub-levels: (1) Primary Function: sense of security; (2) Secondary function: sense ofpower/ownership; (3) Territory Function: sense of esteem, establish identity, self-image and recognition/self-actualization.This research was conducted through: (1) A literature review that explores the concept of territoriality in architecture:characteristics, functions and classification of territoriality; (2) Observations to understand the concept of territorialitythat formed in some horizontal or vertical housing, especially low-cost housing in Jakarta – Indonesia.